Families Mental Health and Challenges in the 21st Century Proceedings of the 1st International Conference of Applied Psychology on Humanity (ICAPH 2022), Malang, Indonesia, 27 August 2022 - Arifin, Syamsul; Yuniardi, Salis; Karmiyati, Diah; Iswinarti; Hasanati, Nida; Winarsunu, Tulus; Suryaningrum, Cahyaning (Taylor & Francis, 2024)
Families Mental Health and Challenges in the 21st Century contains the papers presented at the 1st International Conference of Applied Psychology on Humanity 2022 (ICAPH 2022, Malang, Indonesia, 27 August 2022). The contributions focus on the challenges in micro-family environments that are faced with rapid developments of technology and information in the 21st century. The issues addressed in the book include: Family Strengthening Principles and Practices Children and Woman Protection Family Resilience Crisis and Challenge Families Mental Health and Challenges in the 21st Century is of interest to professionals and academics involved or interested in psychology, the field of mental health and related disciplines.